1994
DOI: 10.3109/01050399409047503
|View full text |Cite
|
Sign up to set email alerts
|

Extended High-frequency Audiometry: Air- and Bone-conduction Thresholds, Age and Gender Variations

Abstract: Air-conduction and bone-conduction thresholds have both been determined in the conventional audiometric frequency ranges and in the extended high frequencies through respectively 18 and 16 kHz for otologically healthy subjects in different age groups covering the age span 8-14 years through the eighth decade. Subjects younger than 30 years had conventional frequency air-conduction thresholds < or = 10 dB HL, whereas the corresponding thresholds of older subjects were within 0.1 and 0.9 percentiles of ISO 7029 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
22
0

Year Published

1998
1998
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 21 publications
3
22
0
Order By: Relevance
“…Exactly the same finding was reported by Lee et al (2012), but they hypothesized that the method of depth-compensation, (which eliminates the influence of ear canal size) was the reason. Hallmo et al (1994) found no significant difference in air conduction in the high-frequency range as well.…”
Section: Hearing Threshold Fittingmentioning
confidence: 81%
See 1 more Smart Citation
“…Exactly the same finding was reported by Lee et al (2012), but they hypothesized that the method of depth-compensation, (which eliminates the influence of ear canal size) was the reason. Hallmo et al (1994) found no significant difference in air conduction in the high-frequency range as well.…”
Section: Hearing Threshold Fittingmentioning
confidence: 81%
“…However, in the ISO 7029 (2000) standard, a is specified only for frequencies ranging from 125 Hz to 8 kHz and, even in the most recent version of this standard (2000), no a coefficients for frequencies higher than 8 kHz are presented. As already noted by Hallmo et al (1994), there has not been any standard available for changes of high-frequency hearing associated with aging. The ISO 7029 (2000) standard was created on the basis of the work of Robinson and Sutton (1979).…”
Section: Introductionmentioning
confidence: 91%
“…Lö ppö nen et al (1991) also reported gender effects at higher frequencies (8000 through 18 000Hz) with females displaying better thresholds than males, especially in the age range of 40 through 60 years. Similarly, Hallmo et al (1994) reported that females generally had more sensitive hearing than males in groups older than 24 years for frequencies from 8000 through 18 000 Hz. However, their findings were only significant for bone conduction thresholds at 9000 Hz in the group aged 50 through 59 years.…”
Section: Discussionmentioning
confidence: 94%
“…These studies, although the amount and level of exposure varied, generally have shown that Caucasians have poorer behavioral thresholds than African Americans (Henselman et al, 1995;Ishii & Talbott, 1998;Karsai et al, 1972;Royster et al, 1980b). Regarding gender influences, some studies have shown that females generally have more sensitive hearing than males (Hallmo et al, 1994;Lö ppö nen et al, 1991;Stelmachowicz et al, 1989) , while others have shown no gender differences (Betke, 1991;Dunckley & Dreisbach, 2004;Frank, 1990;Osterhammel & Osterhammel, 1979).…”
Section: Sumariomentioning
confidence: 92%
“…The introduction of high frequency audiometry (HFA) to health inspection protocols for noise-exposed individuals could detect those workers predisposed to HLIHSPL even before they are diagnosed with changes through conventional audiometric exams, since many studies point to the increase in high frequency thresholds in workers exposed to noise 5,[7][8][9] . Contrary to conventional audiometry, where we can classify the loss into mild to profound, high-frequency audiometry does not have standardized results.…”
Section: Introductionmentioning
confidence: 99%